2016
DOI: 10.1109/tit.2016.2595586
|View full text |Cite
|
Sign up to set email alerts
|

Projection Theorems for the Rényi Divergence on $\alpha $ -Convex Sets

Abstract: This paper studies forward and reverse projections for the Rényi divergence of order α ∈ (0, ∞) on α-convex sets. The forward projection on such a set is motivated by some works of Tsallis et al. in statistical physics, and the reverse projection is motivated by robust statistics. In a recent work, van Erven and Harremoës proved a Pythagorean inequality for Rényi divergences on α-convex sets under the assumption that the forward projection exists. Continuing this study, a sufficient condition for the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Second, even if D(P C) = ∞, the Rényi divergence D α (P Q) (see e.g. [20]) may be a well-defined non-negative real number for α ∈ (0, 1) and Q ∈ C. These Rényi divergences are jointly convex in P and Q [20] and for each 0 < α < 1 one may define a reversed Rényi projection Qα of P on C [21]. If it exists, it can be shown that this distribution will satisfy…”
Section: Future and Related Workmentioning
confidence: 99%
“…Second, even if D(P C) = ∞, the Rényi divergence D α (P Q) (see e.g. [20]) may be a well-defined non-negative real number for α ∈ (0, 1) and Q ∈ C. These Rényi divergences are jointly convex in P and Q [20] and for each 0 < α < 1 one may define a reversed Rényi projection Qα of P on C [21]. If it exists, it can be shown that this distribution will satisfy…”
Section: Future and Related Workmentioning
confidence: 99%